Inducing Drought Resilience in Maize Through Encapsulated Bacteria: Physiological and Biochemical Adaptations - Tiago Lopes; Pedro Costa; Paulo Cardoso; José Almeida e Silva; Etelvina Figueira (Plants)
Droughts are projected to become prevalent throughout the 21st century, endangering agricultural productivity and global food security. To address these challenges, novel strategies to enhance water management and augment plant resilience are imperative. Bacterial encapsulation has emerged as a promising approach, offering benefits such as enhanced bacterial survival, soil compatibility, and sustainable plant growth. This study evaluated the osmotolerance of bacteria from arid environments and determined their plant growth-promoting ability in drought conditions. The encapsulation of these bacteria in bio-compatible capsules led to a substantial enhancement in the performance of maize plants under drought stress. Maize plants treated with encapsulated bacteria demonstrated a 35% increase in root biomass and a 28% enhancement in shoot growth compared to untreated controls. Furthermore, significant physiological and biochemical adaptations were observed, including a 45% increase in photosynthetic pigment concentration and higher osmolyte levels, which contributed to improved drought stress tolerance. The findings of this study demonstrate the potential of encapsulated bacteria to enhance maize resilience to drought, thereby supporting robust growth under water-limited conditions. This approach presents a sustainable strategy to improve drought tolerance, and it may reduce irrigation dependency and maintain crop yields in the face of increasing climate uncertainty.